Rationalizing Mongolia hospital services experiences, lessons learned, and future directions - Jigjidsuren, Altantuya (East Asia working papers., 2021)
Before the 1990s, Mongolia had a health care system that largely depended on hospital based services characterized by the extensive use of an excessive number of acute beds, a large number of medically unjustified admissions, and lengthy hospital stays. In the early 1990s, the Government of Mongolia started socioeconomic reforms as part of the transition to a market economy. Since then, ADB has been supporting health sector reforms in the country.